1999
DOI: 10.1116/1.590515
|View full text |Cite
|
Sign up to set email alerts
|

Interface charge and nonradiative carrier recombination in Ga2O3–GaAs interface structures

Abstract: Recombination, gain, band structure, efficiency, and reliability of 1.5-μm GaInNAsSb/GaAs lasers J. Appl. Phys. 97, 083101 (2005); 10.1063/1.1873035 Investigation of the annealing effect on the nonradiative carrier recombination in AlGaAs/GaAs utilizing the piezoelectric photothermal technique Rev. Sci. Instrum. 74, 550 (2003); 10.1063/1.1515888A comparative study of spontaneous emission and carrier recombination processes in InGaAs quantum dots and GaInNAs quantum wells emitting near 1300 nmWe have investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…The results can be readily understood in connection with previous results of Passlack et al 3 and Droopad et al 5 who have found that with proper growth conditions, a crystalline Ga 2 O layer is formed at the interface between the Ga 2 O 3 film and GaAs. Indeed such crystallization improves the interface.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…The results can be readily understood in connection with previous results of Passlack et al 3 and Droopad et al 5 who have found that with proper growth conditions, a crystalline Ga 2 O layer is formed at the interface between the Ga 2 O 3 film and GaAs. Indeed such crystallization improves the interface.…”
supporting
confidence: 70%
“…The understanding and engineering of the properties of the interface between an insulator film and a III-V(100) compound semiconductor are very important for the development of various devices. [1][2][3][4][5][6][7][8] In particular, silicon dioxide (SiO 2 ) and silicon nitride (SiN x ) layers are routinely deposited onto GaAs(100) and other III-V(100) semiconductors at different steps of device processing. [9][10][11] For example, these dielectrics are used for surface protection, electrical insulation in laser diodes, antireflection coatings, and distributed Bragg reflectors, and for selective quantum well (QW) intermixing.…”
mentioning
confidence: 99%
“…Successful development of such a gate dielectric would also open up a wide range of applications in the wireless and optoelectronic arenas. Gallium oxide on GaAs represents one of the candidates for such gate dielectric application as it has demonstrated an unpinned Fermi level on GaAs with low density of interfacial states as originally determined by scanning tunneling spectroscopy (STS) [12] and photoluminescence-intensity (PL-I) measurements [13,14]. However, the relatively small conduction band offset of Ga 2 O 3 on GaAs necessitates the use of a dielectric stack structure such as Ga 2 O 3 /Gd x Ga 1 À x O 3 [15] for admittance-voltage characterization of the Ga 2 O 3 /GaAs interface and MOSFET applications.…”
Section: Introductionmentioning
confidence: 99%
“…The GaAs epitaxial layer structure is optimized for electrical Ga 2 O 3 -GaAs interface characterization using a PL intensity technique. [8][9][10] Effusive evaporation from a polycrystalline Ga 2 O 3 source material allows the deposition of stoichiometric Ga 2 O 3 films with impurity levels below 10 19 cm Ϫ3 . The typical oxide volume density is 5.6 g/cm 3 and the oxide film thickness t ox ranges from 78 -727 Å in this study.…”
Section: Thermally Induced Oxide Crystallinity and Interface Destructmentioning
confidence: 99%